Urban safety and psychological distress during the pandemic: the results of a longitudinal study - Ferretti, Fabio; Gualtieri, Giacomo; Masti, Alessandra; Uvelli, Allison (Frontiers in Psychology, 2024)
In the last decades, a large body of literature has explored the topic of perceived safety and fear of crime in urban environments. The effects of psychological factors on such feelings have been studied, but rarely using prospective studies, and never when these factors intercept a worldwide dramatic event like the pandemic. This research aimed to analyse the variations of the feelings of urban safety during the pandemic, the role of resiliency and the effect of psychological stressors such as anxiety, stress, and depression.During 2019 and 2022, before and after the pandemic, a face-to-face interview was administered to the same group of 195 participants. The PUSAS scale was used to measure unsafety, the ER89-R to assess for resiliency, the DASS-21 to collect data about the general distress (anxiety, stress and depression), and the CAS scale was used to evaluate the specific coronavirus anxiety. Structural equation models were applied to test a theoretical framework grounded on the relationships between these measures.The research findings showed decreased feelings of unsafety across the pandemic, consistent with the literature. The positive effect of ego-resiliency was significant but only for its interaction with data collected before the pandemic, whilst stress and anxiety impacted unsafety in 2022 through different pathways. None of the symptoms of general distress influenced the concern about crime and sense of vulnerability, as the feelings of unsafety were found independent from the variations of the specific coronavirus anxiety.Although the research findings did not confirm the impact of coronavirus, they presented some facets that disconfirm what the literature reported about the relationships between psychological distress and fear of crime. Implications about measurement issues are discussed.